The Influence of Entrepreneurial Motivation and Entrepreneurial Alertness on Entrepreneurial Intentions: The Dominant Role of Alertness among Student Entrepreneurs - Yoan Fadhila Erine; Efni Cerya (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2026)
Objective: This study aims to examine the effect of entrepreneurial motivation and entrepreneurial alertness on business success among university students, with a focus on identifying which factor plays a more significant role in achieving business outcomes. Method: A quantitative approach was employed using a survey method. Data were collected through questionnaires measured on a 5-point Likert scale. The analysis was conducted using multiple linear regression to determine the partial effects of each independent variable on business success. Results: The findings indicate that entrepreneurial alertness has a significant positive effect on business success. In contrast, entrepreneurial motivation does not show a significant partial effect (p = 0.122). This suggests that the ability to recognize and exploit business opportunities is more influential than motivation alone in determining business success among students. Novelty: This study provides additional empirical evidence highlighting the critical role of entrepreneurial alertness in student entrepreneurship. It emphasizes that motivation, although important, may not always translate into tangible business outcomes without the capability to identify opportunities. The study also contributes to the literature by focusing on a student sample, offering insights for developing more effective entrepreneurship programs.